Dynamic Load Test and Contact Force Analysis of the AERORail Structure - Fangyuan Li; Zhenwei Guo; Yunxuan Cui; Peifeng Wu (Applied Sciences, 2023)
The flexible structure of the new type of aerial track studied in this paper is formed by strings and tracks, which have obvious dynamic characteristics under the action of vehicle moving loads and is also an important factor affecting its performance. The paper uses the full-scale model of AERORail, based on the modal test under a specific span, combined with the fundamental frequency analysis of the structure, and carries out the dynamic load test to determine the change law of the contact force acting on the rail by the dynamic load. The time-domain improved algorithm based on the method of moments is used to identify and analyze the dynamic loads under different spans and vehicle speeds and to determine the correlation between the dispatched loads and the spans and vehicle speeds. It is proven that the occurrence time and frequency of the contact force are related to the passing time of the vehicle. The contact force fluctuates with the change in the vehicle speed, but with the increase in the span, the fluctuation of the contact force decreases obviously. The relevant conclusions provide support for the layout of the AERORail vehicle load. For this innovative structure, the relevant conclusions provide the basis for the application of this novel structure.